Engineering insightful visualizations. (December 2016) - d'Auriol, Brian J.
Abstract: A theoretical visualization model that is suitable for a guideline based engineering approach as well as generically and widely applicable to visualization and its subfields is developed in this work. It is based on investigating question–answer pairs and emphasizes understanding and knowledge acquisition achieved via insight and learning but which is impeded by confusion brought on by in-appropriateness, incoherence, anacolutha and non-sequiturs. These terms are technically defined within the model. A visualization metric is developed that relates insight, learning and confusion with characteristics of how much and how fast understanding and knowledge are acquired. The model entails two connected processes: a visualization process based on visualization media componentization followed by a human process consisting of perception, interpretation, understanding and knowledge acquisition. Several case studies drawn from the various subfields of visualization show the potential of the proposed model. Abstract : Graphical abstract: